Preparation and characterization of high temperature resistant thermosetting polyphenylene ether resin. Issue 39 (12th August 2022) - Wu, Xiankun; Xu, Chang‐an; Lu, Mangeng; Wang, Kunxin; Li, Zhao; Yang, Hui
Abstract: To explore high thermal properties, low dielectric constant and loss for copper clad laminates, poly(phenylene oxide) (PPE) with different end groups (allyl and epoxide groups) were successfully prepared. Firstly, low molecular weight polyphenylene ether was synthesized using the redistribution method. Then the polyphenylene ether thermosetting polymers by modifying their terminal hydroxyl groups were reported and their fundamental materials properties were compared. Through property tests and data analyses, it was found that PPE with vinyl end groups had the best performances, especially high glass transition temperature (about 230°C), the thermal conductivity was 0.32–0.38 Wm −1 K −1, low dielectric constant (about 2.5) and low dielectric loss (about 4.4 × 10 −3 ). The possible reason was that the main chain of polyphenylene ether contains non‐polar crosslinkable group (CC). In a word, through properties comparison of thermosets of PPE, the results demonstrated that the materials of all systems were suitable for using as printed circuit boards. Abstract :